Knowledge, Practices, and Attitudes towards Breast Cancer Prevention among Church Members in Silang, Philippines - Janet Nyaboke Odhiambo (Adventist University of Africa, 2023)
Background: Breast cancer remains a significant public health concern, making prevention strategies crucial. This study assessed women's knowledge, practices, and attitudes towards breast cancer prevention. Methods: A quantitative survey using a one-group pre-test and post-test design was conducted. Results: The results showed that the women surveyed had a good level of knowledge about breast cancer and its risk factors. However, they lacked knowledge about healthy food choices, serving portions, and recommended caloric intake. Despite their positive attitudes towards mammogram screenings, many women did not engage in regular screenings. Factors such as fear, inconvenience, and lack of access to healthcare resources hindered the translation of positive attitudes into action. Conclusion: The study highlights the need for targeted interventions to bridge the gap between knowledge and practice in breast cancer prevention. Educational initiatives, improved access to mammogram screenings, and efforts to alleviate fear and inconvenience barriers can enhance the effectiveness of preventive measures in reducing breast cancer morbidity and mortality.